Geologia do platô N6 - província mineral de Carajás (SP) - Motta, João Gabriel [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The N6 Plateau presents an iron-ore occurence in Carajás Mineral Province, standing near to actually operating deposits. Geological mapping in 1:10,000 scale and integration of geochemical, geophysical, petrography and drilling turns possible interpretation of his geological evolution. The mapped area has lithotypes from Archean Grão Pará Group, comprising very lowgrade metamorphic basic rocks and iron formation and an Proterozoic sedimentary association of conglomeratic sandstones called as Caninana Unity. The structural geology in given by a regional scale homoclinal, where the Grão Pará Group strata dips towards SW, as a part of the Northern Limb of the Carajás Fold. Subsequent deformation associated to the installation of the Carajás Shear Zone presents as E-W fold axis. Geochemical evidence permits to consider de Parauapebas Formation as the rocks which has been hydrothermally-altered to outsourcing fluids responsible to deposition of iron formations in the oceanic system, including different signatures which can be interpreted as possible sub-embayments in the Carajás Basin. The iron ore in the area occurs in subsurface as very fine friable hematite generated by supergenous enrichment of the iron formation. The conceived geologic model differs from the current academic proposal on the fact that hydrothermal alteration has been involved on the jaspelite enrichment. Metamorphism on the Parauapebas Formation presents paragenesis considered as ocean-floor metamorphism which precedes de deformation insofar as the rocks show no tectonic fabric referring to shallow crust evolution. Geophysical methods such as magnetometry and gravimetry presents excellent results for structural interpretation in uneven exposed terrain

O Platô N6 representa uma ocorrência de minério de Ferro no interior da Província Mineral de Carajás, estando adjacente a depósitos atualmente em operação. Seu mapeamento geológico na escala 1:10.000 e integração de dados geoquímicos, geofísicos, petrográficos e sondagens possibilitaram uma interpretação acerca de sua evolução geológica. A área mapeada apresenta litotipos do Grupo Grão Pará, de idade arqueana, compreendendo rochas metabásicas de grau metamórfico muito baixo e formações ferríferas e uma associação sedimentar proterozóica composta por arenitos conglomeráticos da Unidade Caninana. A estrutura da área se dá por um homoclinal de ampla escala, onde os estratos do Gr. Grão Pará mergulham para SW, concordante como parte do flanco Norte da Dobra de Carajás. Deformação posterior associada à instalação da Zona de Cisalhamento Carajás se faz presente por eixos aproximadamente E-W. Evidências geoquímicas permitem considerar a Fm. Parauapebas como a rocha que foi lixiviada por fluidos hidrotermais que foram responsáveis pela formação das formações ferríferas no sistema oceânico, permitindo observar assinaturas diferentes levando a considerar a possibilidade de subembaciamentos na Bacia Carajás. O minério de ferro encontrado em subsuperfície corresponde a hematita friável de granulação fina, formada a partir do enriquecimento supérgeno sobre as formações ferríferas. O modelo geológico concebido discorda da proposta corrente na literatura onde haveria atividade hidrotermal envolvida no enriquecimento dos jaspilitos. O metamorfismo registrado pela Formação Parauapebas apresenta paragêneses que podem ser consideradas como produto de metamorfismo de fundo oceânico e, portanto, anterior à deformação incidente, visto que a deformação não registra fabric, remetendo a uma possível situação de evolução de crosta rasa... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Metalogenia; Minerios de ferro; Mapeamento geologico; Geologia economica - Brasil; Carajas, Serra dos (PA); Metallogeny; Carajás Mountains (Brazil); Geological mapping; Geology, Economic; Iron ores